Interactive effect of tillage and crop residue management on weed dynamics, root characteristics, crop productivity, profitability and nutrient uptake in chickpea (Cicer arietinum L.) under Vertisol of Central India. - Kaushlendra Pratap Singh; Vasudev Meena; J Somasundaram; Suchi Singh; Mohan Lal Dotaniya; Hiranmoy Das; Ompal Singh; Ajay Srivastava (PLoS ONE, 2022)
Tillage and crop residue management play an imperative role in soil physico-chemical properties that eventually affects crop productivity. The objective of the study to find out a compatible combination of tillage and crop residue management for achieving sustainable food production by improving soil properties, providing favorable environment to crop plants. Secondly, managing crop residues effectively to reduce environmental pollution arising due to crop residue burning. With this aim, a field experiment was conducted on six years continued running experiment under conservation agricultural practices during rabi season of 2019-20 on chickpea. The experiment was comprised of five tillage operations with or without crop residue in main plot and three levels of nutrients in sub plots laid out in split plot design with three replications. Reduced Tillage with 60cm residue height (RT60) was recorded higher growth and yield attributes over conventional tillage practice that attributed to economic yield enhancement. The percent yield increment under NT and RT with 30 and 60cm height residue retention varied from 6.91% to 9.67% over conventional tillage. Maximum grain (2380 kg ha-1) and biological output (5762 kg ha-1) was recorded under RT60 (T4), which ascribed to higher net return (Rs 60551 ha-1) and benefit-cost ratio (2.97). The augmentation in net monetary benefit among tillage systems was lies between 24.32% to 37.78% over conventional tillage. The seed protein content ranged between 20.38 to 21.69% among the treatments. Moreover, total N uptake was maximum under RT60, while total P and K uptake was higher in No Tillage with 30cm residue height (T1). No-Tillage with 60cm residue height (NT60) recorded relatively higher soil moisture content (SMC) (22.71 and 15.40%). Treatment NT30 accrued relatively higher value of soil bulk density (1.42 Mg m-3) followed by NT60 and RT60 in comparison to conventional tillage (1.34 Mg m-3). In conclusion, NT and RT with 60cm residue height along with STCR (N3) nutrient dose was found effective for sustainable food production.